Buyer Behavior Model as a Prerequisite for a Marketing Strategy for Forming Consumer Loyalty (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The purpose of the article is to investigate the most widespread patterns of buying behavior that are found inscientific literature, and to offer their vision of a buyer behavior model as a prerequisite for a marketing strategy for the formation of consumer loyalty.Theoretical and methodological analysis were based on the scientific works of domestic and foreign scholars on the theory of marking, behavioral theory, neurobiology.The prospect of future research should be the development of an algorithm for adaptation of the model ofconsumer behavior proposed in the work to develop and implement a marketing strategy for the formation of consumer loyalty.The approaches proposed in the work can be taken into account by the marketing services of domestic enterprises in studying and developing measures to meet the needs of existing and existing consumers and customers. Generalized scientific approaches to the model of purchasing behavior of the buyer as a prerequisite for the marketing strategy of forming consumer loyalty; described the most common models of purchasing behavior; analyzed and implemented a comparative description of the most common models of buying behavior, in particular classical behavior, which is based on the process of externalization of entropy (external uncertainty), the theory of meaningful behavior, «heuristics of conformity with individual characteristics» and others; it is noted that none of the existing models of buying behavior in the scientific literature is ideal, and therefore there is a risk and uncertainty; therefore, in order to take into account the limited risk, it is necessary to introduce a nonlinear function into the system of constraints; minimizing the risk of a certain process is achieved by studying a mathematical model with a nonlineartarget function; on the basis of previous analysis a new vision of a model of buying behavior has been formed; by exploring and shaping the benefits of a purchasing behavior model, you can provide goods and services that meet their inquiries, thus, loyalty of consumers will be formed; stressed the necessity of applying the situational approach in substantiating the choice of the model of purchasing behavior.It is concluded that in the future, those companies will be competitive which constantly and consistently payattention to the relationship between loyalty and level of customer satisfaction; on the basis of the previous analysis; the key factor of long-term success of the enterprise will be loyalty.
Keywords: model, purchasing behavior of the buyer, consumer loyalty, marketing strategies